Environmental Assessment For Small- And Medium-scale Road Projects Implemented In Local Authority Areas: A Case Study From Thailand - Trethanya, Suparb; Perera, Ranjith (Penerbit Universiti Sains Malaysia, 2009)
In developing countries like Thailand, an Environmental Assessment (EA) is conducted only for projects prescribed by environmental legislation. Numerous projects, especially those that are small- and medium-scale in size and scope, are implemented in areas by a local authority without any type of EA. Based on a comparative analysis of the environmental status of large-, medium- and small-scale road development projects implemented by a local authority in Thailand, this paper attempts to justify the enforcement of EAs for medium- and small-scale projects. The justification is mainly based on the perceptions of people affected by these projects. Environmental impact scores, computed on the basis of people’s perceptions, reveal that, irrespective of the size of a project, the impacts caused by different sized projects are perceived as similar. Since every development project is implemented for the purpose of human development, this paper proposes to integrate environmental screening and initial EAs into the existing development control measures enforced by urban planning regulations and laws.